Survey of cucumber target spot, in vitro sporulation and aggressiveness of Corynespora cassiicola - Herman Fischer, Ivan; Meleiro Da Silva, Lucas; Pelizzaro Morales, João Vitor; Cagnim Martins Parisi, Marise; Amorim, Lilian (Comunicata Scientiae, 2022)
The objective was to carry out a survey of the occurrence of the target spot (Corynespora cassiicola) in cucumber crops in São Paulo State; to evaluate culture media for sporulation of the pathogen and the aggressiveness of isolates of the pathogen in cucumber plants. The target spot was found in nine municipalities, being the main disease in seven of the ten municipalities sampled, with leaf incidence above 50%, showing that the target spot of cucumber is widely distributed in São Paulo State. Other diseases found less frequently were scabies (Cladosporium cucumerinum), alternaria spot (Alternaria cucumerina), cercospora spot (Cercospora citrullina) and downy mildew (Pseudoperonospora cubensis), predominant in samples from one or two municipalities, but also found in most municipalities. The zoned spot (Leandria momordicae) was found to have a low incidence, in samples from three municipalities and with an incidence lower than 20%. Greater sporulation of the pathogen occurred in tomato juice and oat flour media, without scraping the surface of the colony maintained for 16 days at 25ºC, under continuous fluorescent light. The germination of C. cassiicola isolates used in the aggressiveness test was between 82.8 and 95.5%, with the 50 isolates separated into two groups. The isolates were separated into four groups within the range of 3.1 to 22.3% in severity, after ten days of inoculation of the pathogen, showing the genetic variability within the species, which should be considered in management studies, such as genetic improvement.